Influence Social Media Marketing, Influencer Marketing, dan Brand Image on the Purchase Decision of Lemonilo Brownies Crispy Products in Surabaya - Aprilia, Firnanda Dwi; Nugroho, Rusdi Hidayat (Universitas KH. Abdul Chalim Mojokerto, 2025)
The transformation of information and communication technology in the business world has a significant influence, encouraging food product companies and others to utilize the media as a tool in marketing. This study aims to find out howsocial media marketing, influencer marketing And brand imagehas an influence on consumer purchasing decisions on Lemonilo Brownies crispy products. This study is a quantitative study with a questionnaire survey approach through operational definitions of variables conducted on Lemonilo Brownies crispy Surabaya products. The results of the study indicate thatSocial Media Marketing, Influencer Marketing, and Brand Imagesimultaneously has a significant influence on the purchasing decision of Lemonilo Brownies Crispy products, and Social Media Marketing, Influencer Marketing, and Brand Image partially also has a positive and significant influence on purchasing decisions.